Exercise training during normobaric hypoxic confinement does not alter hormonal appetite regulation. - Tadej Debevec; Elizabeth J Simpson; Ian A Macdonald; Ola Eiken; Igor B Mekjavic (PLoS ONE, 2014)
Both exposure to hypoxia and exercise training have the potential to modulate appetite and induce beneficial metabolic adaptations. The purpose of this study was to determine whether daily moderate exercise training performed during a 10-day exposure to normobaric hypoxia alters hormonal appetite regulation and augments metabolic health.Fourteen healthy, male participants underwent a 10-day hypoxic confinement at ∼ 4000 m simulated altitude (FIO2 = 0.139 ± 0.003%) either combined with daily moderate intensity exercise (Exercise group; N = 8, Age = 25.8 ± 2.4 yrs, BMI = 22.9 ± 1.2 kg · m(-2)) or without any exercise (Sedentary group; N = 6 Age = 24.8 ± 3.1 yrs, BMI = 22.3 ± 2.5 kg · m(-2)). A meal tolerance test was performed before (Pre) and after the confinement (Post) to quantify fasting and postp randial concentrations of selected appetite-related hormones and metabolic risk markers. 13C-Glucose was dissolved in the test meal and 13CO2 determined in breath samples. Perceived appetite ratings were obtained throughout the meal tolerance tests.While body mass decreased in both groups (-1.4 kg; p = 0.01) following the confinement, whole body fat mass was only reduced in the Exercise group (-1.5 kg; p = 0.01). At Post, postprandial serum insulin was reduced in the Sedentary group (-49%; p = 0.01) and postprandial plasma glucose in the Exercise group (-19%; p = 0.03). Fasting serum total cholesterol levels were reduced (-12%; p = 0.01) at Post in the Exercise group only, secondary to low-density lipoprotein cholesterol reduction (-16%; p = 0.01). No differences between groups or testing periods were noted in fasting and/or postprandial concentrations of total ghrelin, peptide YY, and glucagon-like peptide-1, leptin, adiponectin, expired 13CO2 as well as perceived appetite ratings (p>0.05).These findings suggest that performing daily moderate intensity exercise training during continuous hypoxic exposure does not alter hormonal appetite regulation but can improve the lipid profile in healthy young males.